2013
DOI: 10.1002/ijc.28345
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Muc5AC expression is associated with poor prognosis in gastric cancer

Abstract: Mucins reportedly play numerous key roles in carcinogenesis, including in tumor invasion, regulation of differentiation and tumor cell proliferation. We investigated the effect of Muc5AC, a secreted mucin, on the invasiveness=migratory capability of gastric cancer cells and the prognostic significance of Muc5AC in gastric cancer patients. The clinicopathological and prognostic significance of Muc5AC expression was validated using immunohistochemical analysis in 412 gastric cancer patients. Differential gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 22 publications
2
23
1
Order By: Relevance
“…In contrast, in gastric cancer where MUC5AC is heavily expressed under normal condition, a decrease in MUC5AC during pathologic development from the high expression normal level is associated with a poor prognosis 17 . Normal pancreatic ductal epithelia show no MUC5AC expression 10 .…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, in gastric cancer where MUC5AC is heavily expressed under normal condition, a decrease in MUC5AC during pathologic development from the high expression normal level is associated with a poor prognosis 17 . Normal pancreatic ductal epithelia show no MUC5AC expression 10 .…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, decreased MUC5AC expression was associated with increased aggressiveness of gastric cancers, including tumor invasion and lymph node metastasis, which indicated that MUC5AC has a distinct function in different cancers. 22 However, the mechanism of mucins in the development of cancer has not been well clarified. Deregulation of transmembrane mucine (e.g., MUC1) is involved in constitutive activation of growth and survival pathways such as the Wnt/b-catenin and nuclear factor-jB pathways through their CT for the survival and proliferation of tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these backgrounds, we focused on MUC5AC , which is a well-established gastric marker gene [6], [14] and is often used for the clinical assessment of gastric cancer [15]. There have been many previous reports investigating the expression of MUC5AC and prognosis of gastric cancer, but the association between expression of MUC5AC and malignant potential of gastric cancer is still controversial [16], [17], [18], [19]. Nevertheless, MUC5AC is one the most evident gastric marker clearly decreased in the process of intestinal metaplasia [14], [20].…”
Section: Introductionmentioning
confidence: 99%